A new approach for examination of performance of interior lighting systems - EKREN, NAZMİ (ELSEVIER SCIENCE SA, 2014)
This paper presents a new approach for examination of insufficiency of a current lighting system and for performing maintenance plans of a lighting installation. Thus, a numerical algorithm based on finite element method (FEM) that ensures the required accuracy for illuminance calculations according to international lighting standards was developed. Experimental measurements were recorded in a controlled environment for the purpose of measuring the effectiveness of the algorithm. The average illuminance calculated according to CIBSE Code 1994 published by the Chartered Institution of Building Services Engineers (CIBSE) was obtained by error of 5.3% compared to the experimental measurements. Illuminance values of 894 points were calculated as 0.3% error according to the actual experimental measurements by proposed numerical algorithm that uses 36 pieces measurement data. Less experimental measurements provided more accurate results. The results obtained indicate that the suggested numerical model is very effective and usable in calculations of illuminance. In this way, this model will eliminate the requirement for long experimental measurements in lighting system controls that must be carried out periodically. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Illumination; Illuminance; FEM; Lighting system lifetime; Lighting system maintenance